Physicochemical Characterization and Heavy Metal Contents of Stingless Bee Honey (Trigona itama) from Bekalar Village, Riau - Wahyu Ramadhan; Dela Agung Septriady; Diana Santi (Lembaga Pengembangan Kinerja Dosen, 2026)
Honey is a natural product rich in simple sugars and minor bioactive constituents and is widely recognised for its antioxidant, antibacterial, anti-inflammatory, and wound-healing activities. Stingless bee honey from Trigona itama has become increasingly relevant in Southeast Asia due to its distinctive physicochemical profile and its high content of phenolics and flavonoids, which contribute to functional properties compared with conventional Apis dorsata honey. Despite its growing economic and scientific importance, standardized data on the quality and safety of Trigona itama from specific local environments in Indonesia remain limited. This study evaluated the physicochemical characteristics and heavy metal content of Trigona itama honey originating from Bekalar Village, Siak Regency, Riau, and assessed the quality standards of honey with Standar Nasional Indonesia (SNI) 8664:2018 for honey. A descriptive laboratory design was employed, and honey samples from managed colonies were analysed for moisture, acidity ash content, viscosity, and heavy metal content of Pb, Cd, Hg, and As using validated analytical procedures. The honey demonstrated a moisture content of 28.39 ± 0.03%, acidity content 30.90± 4,74 mLNaOH/Kg, ash content of 0.073 ± 0.03% b/b, viscosity of 68,44 ± 0,725 poise. Heavy metal concentrations were low, with Pb < 0.22 mg/kg, Cd < 0.01 mg/kg, Hg < 0.002 mg/kg, and As < 0.30 mg/kg. These findings confirm that Trigona itama honey from Bekalar village is safe and compositionally consistent with typical stingless bee honey due to Standar Nasional Indonesia (SNI) 8664:2018 for honey, although its high moisture content underscores the need for improved post-harvest handling to support stability and compliance with national quality requirements.